Ukraine Jobs study : Fostering Productivity and Job Creation, Volume 1 - World Bank (Washington, DC, 2012)
This Ukraine Jobs Study aims to 1) assess labor market performance in the Ukraine, 2) identify key constraints to job creation, and suggest policies that will foster job creation and productivity. The study finds that, despite relatively low unemployment, the labor market is depressed and productive job opportunities are scarce. Moreover, unemployment is likely to increase once enterprise restructuring accelerates. The primary cause of poor labor market outcomes in Ukraine is the small size of the "new" private sector, consisting of small firms. This, in turn, is due to the poor investment climate caused by high risks, costs, and barriers associated with doing business in the Ukraine. Accordingly the key to improving labor market outcomes is to remove the main impediments to entry and growth, such as policy uncertainty, corruption, red tape, inefficient regulations, and poor access to finance. In the longer term, labor market institutions need to be reformed to create an adaptable labor market that supports job creation and growth in productivity.